Heavy metal discharge into Lake Victoria : a study of the Ugandan cities of Kampala, Jinja and Entebbe - Ljung, Karin (SLU/Dept. of Soil Sciences, 2002)
Water samples from different sampling sites located in the Ugandan cities of Kampala, Jinja and Entebbe as well as the remote Ssese Islands, were analyzed for concentrations of Cd, Cr, Cu, Ni, Pb and Zn. Both Kampala and Jinja have large industrial areas while Entebbe has Uganda's largest airport. Household and industrial wastes are discharged into Lake Victoria largely untreated. The objectives of this study were to: 1) evaluate concentrations of the metals in discharge from the selected sites; 2) determine whether or not wetlands impacted on the magnitude of metal discharge into the lake, 3) determine and assess heavy metal levels in drinking and irrigation water; 4) evaluate heavy metal related risks for humans and the environment.